Acute effects of fatigue on internal and external load variables determining cyclists` power profile - Sanchez-Jimenez, J. L.; Lorente-Casaus, C.; Jimenez-Perez, I.; Gandía-Soriano, A.; Carpes, F. P.; Priego-Quesada, J. I. (Journal of Sports Sciences, 2023)
The aim of the present study was to determine whether fatigue affects internal and external load variables determining power profile in cyclists. Ten cyclists performed outdoor power profile tests (lasting 1-, 5 and 20-min) on two consecutive days, subject either to a fatigued condition or not. Fatigue was induced by undertaking an effort (10-min at 95% of average power output obtained in a 20-min effort followed by 1-min maximum effort) until the power output decreased by 20% compared to the 1-min power output. Fatigued condition decreased power output (p < 0.05, 1-min: 9.0 ± 3.8%; 5-min: 5.9 ± 2.5%; 20-min: 4.1 ± 1.9%) and cadence in all test durations, without differences in torque. Lactate decreased in longer efforts when a fatigue protocol had previously been conducted (e.g., 20-min: 8.6 ± 3.0 vs. 10.9 ± 2.7, p < 0.05). Regression models (r2 = 0.95, p < 0.001) indicated that a lower variation in load variables of 20-min in fatigued condition compared with the non-fatigued state resulted in a lower decrease in critical power after the fatigue protocol. The results suggest that fatigued condition on power was more evident in shorter efforts and seemed to rely more on a decrease in cadence than on torque.